The Effect of NPK-Zeo Fertilizer on Growth and Production of Cucumber (Cucumis sativus L.) in Iwoimopuro Village, Kolaka District - Tanti Anugrah; Musadia Afa; Yolanda Fitria Syahri (Universitas Sembilanbelas November Kolaka, 2017)
The Effect of NPK-Zeo Fertilizer on Growth and Production of Cucumber (Cucumis sativus L.) in Iwoimopuro Village, Kolaka District. This research aimed to determine the effect of liquid fertilizer NPK-ZEO growth and result of cucumbers. This research has taken place in the village Iwoimopuro, District Wolo, Kolaka District. This research is compiled using a Randomized Block Design (RBD). Obser rations were made on plant height, leaf number, age of the plant begins to flower, age of the plant begins to bear fruit, fruit number and fruit weight. The data were processed using the Finger Print Car List (Anova) followed by Least Significant Difference Test (LSD). The results showed that administration of NPK-ZEO significant effect on plant height, leaf number, age of the plant begins to flower, age of the plant begins to bear fruit, fruit number and fruit weight